PENGARUH CLIENT IMPORTANCE, PERGANTIAN AUDITOR, SPESIALISASI INDUSTRI KAP, TIME BUDGET PRESSURE DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Sektor Jasa Infrastruktur, Utilitas dan Transportasi Periode 2015-2017) - Amalina, Carissa; M, Rasuli; Nanda, Mela Fito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine how: 1) the influence of client importance onaudit qualiy 2) the influence of auditor switching on audit quality 3) the influenceof audit firm industry spesialization on audit quality 4) the influence of timebudget pressure on audit quality 5) the influence of firm size on audit quality. Thesample used in this study consisted of 69 samples of Jasa sector infrastructure,utilities, and transport companies listed on the Indonesia Stock Exchange during2015-2017. The sample in this study was taken using a purposive samplingmethod. Data analysis method uses multiple linear regression with the help of acomputer program, namely SPSS version 22.0. The results showed that: 1) ClientImportance has a positive effect on audit quality with a significant value of 0.039<0.05 2) Auditor Switching has no effect on audit quality with a significant valueof 0.510 >0.05 3) Audit Firm Industry Spesialization has a positive effect onsignificant value of 0.033 <0.05 4) Time Budget Pressure has a possitive effect onaudit quality with a significant value of 0.040 <0.05 5) Firm Size has no effect onaudit quality with a significant value of 0,909 <0.05.Keywords : Audit Quality, Client Importance, Auditor Switching, Audit FirmIndustry Spesialization, Time Budget Pressure, and Firm Size